2017
DOI: 10.1371/journal.pone.0175418
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the uptake of persistent identifiers by research infrastructure users

Abstract: Significant progress has been made in the past few years in the development of recommendations, policies, and procedures for creating and promoting citations to data sets, software, and other research infrastructures like computing facilities. Open questions remain, however, about the extent to which referencing practices of authors of scholarly publications are changing in ways desired by these initiatives. This paper uses four focused case studies to evaluate whether research infrastructures are being increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The most evident envisioned advantages of DDPH are: 1. practical use by all participants and stakeholders of the academic publishing process either for confirmation, verification, or evaluation: authors, peer reviewers, publishers, librarians, funders, service and infrastructure providers; 2. fortification of a document's history, centralization of information, and thus transparency through the use of a popular, persistent, unique and actionable tool, the DOI; 3. potential stimulation of the expanded use of DOI to the Chinese literature where the DOI has been weakly adopted (Wang et al, 2018); 4. the downstream fortification of the validity and reliability of a citation or reference (Mayernik and Maull, 2017); 5. as a result of the above advantages, the ability to independently trace if the VoR was manipulated, or not, which may be useful for ethics investigations where a fine-scale appreciation of the historical evolution of a paper might be needed; 6. an open/public tool that allows authors to hold editors and publishers accountable for any manipulative or predatory practices, and vice versa; 7. despite the existence of a wealth of data identification systems, some more elaborate than others (Lee and Stvilia, 2014), to the authors' knowledge, none has yet been able to effectively detect and record changes in VoR, if at all, nor is there a single approach today to support all uses of dynamic data citation formal information associated with a publishing entity, e.g., journal or publisher). 9. an analysis of the information about the most common reasons for making changes to documents is likely to help improve the editorial process and allow editors to avoid common mistakes.…”
Section: Strengths and Weaknesses Of The Doi And Competing Data Stora...mentioning
confidence: 99%
“…The most evident envisioned advantages of DDPH are: 1. practical use by all participants and stakeholders of the academic publishing process either for confirmation, verification, or evaluation: authors, peer reviewers, publishers, librarians, funders, service and infrastructure providers; 2. fortification of a document's history, centralization of information, and thus transparency through the use of a popular, persistent, unique and actionable tool, the DOI; 3. potential stimulation of the expanded use of DOI to the Chinese literature where the DOI has been weakly adopted (Wang et al, 2018); 4. the downstream fortification of the validity and reliability of a citation or reference (Mayernik and Maull, 2017); 5. as a result of the above advantages, the ability to independently trace if the VoR was manipulated, or not, which may be useful for ethics investigations where a fine-scale appreciation of the historical evolution of a paper might be needed; 6. an open/public tool that allows authors to hold editors and publishers accountable for any manipulative or predatory practices, and vice versa; 7. despite the existence of a wealth of data identification systems, some more elaborate than others (Lee and Stvilia, 2014), to the authors' knowledge, none has yet been able to effectively detect and record changes in VoR, if at all, nor is there a single approach today to support all uses of dynamic data citation formal information associated with a publishing entity, e.g., journal or publisher). 9. an analysis of the information about the most common reasons for making changes to documents is likely to help improve the editorial process and allow editors to avoid common mistakes.…”
Section: Strengths and Weaknesses Of The Doi And Competing Data Stora...mentioning
confidence: 99%
“…Another example refers to the PIDs assigned for each specific element within the paper. Even though the paper has a study-level PID [34], it provides specific PIDs to the figure [35], charts [36], and table [37]. These examples show how quickly it is to find a specific fragment of data when having a PID according to the granularity level.…”
Section: The Relevance Of Fine-grained Level Of Data Citation In the ...mentioning
confidence: 99%
“…The first effort within the project was to conduct a case study‐based assessment to evaluate whether research infrastructures are being increasingly identified and referenced in the research literature via persistent citable identifiers. In this study (Mayernik & Maull, ), citations and references for four resources ‐ two data sets, a software package, and a supercomputing facility ‐ were collected manually using Google Scholar searches and analyzed to assess the ways that the resources had been referenced by researchers who used them, by characterizing how often the resources were referenced in papers through in‐text descriptions, mentioned via acknowledgements, or explicitly cited in reference lists. Findings from this study showed how persistent identifiers assigned to the four examined resources were indeed being used in references in published papers on an increasing basis.…”
Section: Investigations Into Linkingmentioning
confidence: 99%